Evaluation of health effect on workers exposed to methyl bromide with prefrontal event-related potential. - Jungmi Choi; Wonseok Cha; Young-Seoub Hong; Min-Goo Park (PLoS ONE)
Methyl bromide (MB) is a potent fumigant used to control pests in soil and agricultural products. As an ozone-depleting substance, MB has been largely replaced by safer alternatives. MB is highly toxic to humans and has been shown to adversely affect asymptomatic workers' central and autonomic nervous systems and vascular health. However, its impact on perceptual and cognitive abilities remains underexplored. In this study, we examined the effects of MB exposure on cognitive functions in asymptomatic workers. Event-related potential (ERP) indices, which reflect perceptual and cognitive processes, and urinary bromide ion (Br-) concentrations were assessed in 32 fumigators (study group) and 18 inspectors (control group) before and after fumigation. Post-work ERP latency and amplitude changes in inspectors were significant (P < 0.01), similar to those observed in healthy individuals. In contrast, ERP changes in fumigators were not significant compared to pre-work values; this suggests that MB negatively impacts cognitive health. Additionally, Br‑ levels in fumigators rose sharply after work (P < 0.001), while inspectors showed no such increase. The elevated Br- levels and nonenhanced ERP indices in fumigators after MB exposure indicate adverse health effects despite the absence of symptoms.